1999
DOI: 10.1515/cclm.1999.043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidized Low Density Lipoprotein, Lipid Mediators and Statins on Vascular Cell Interactions

Abstract: The integrin heterodimer CD11b/CD18 (␣M␤2, Mac-1, CR3) expressed on monocytes or polymorphonuclear leukocytes (PMN) is a receptor for iC3b, fibrinogen, heparin, and for intercellular adhesion molecule (ICAM)-1 on endothelium, crucially contributing to vascular cell interactions in inflammation and atherosclerosis. In this report, we summarize our findings on the effects of lipid mediators and lipid-lowering drugs. Exposure of endothelial cells to oxidized low density lipoprotein (oxLDL) induces upregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 87 publications
1
20
0
1
Order By: Relevance
“…The inhibitory effects of statins on interaction between ECs and PBMCs as shown in adhesion assay are consistent with the previous findings of Weber et al 34 These results suggest that the mechanisms by which statins reduce monocyte adhesion involve, at least in part, the downregulation of integrin expression in HUVECs.…”
Section: Discussionsupporting
confidence: 91%
“…The inhibitory effects of statins on interaction between ECs and PBMCs as shown in adhesion assay are consistent with the previous findings of Weber et al 34 These results suggest that the mechanisms by which statins reduce monocyte adhesion involve, at least in part, the downregulation of integrin expression in HUVECs.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibitors of HMG CoA reductase (a key enzyme of cholesterol synthesis) such as lovastatin interfere with the expression of Mac-1 integrin and block the adhesive function of LFA-1 by direct binding to the I-domain. 154,155 Novel nonpeptide compounds have also been identi®ed for their ability to block ICAM-1/LFA-1 interaction. Through screening a compound library and subsequent optimization of potent ICAM-1/LFA-1 inhibitors, p-arylthio cinnamides with IC 50 values around 35 nM were identi®ed.…”
Section: S T R U C T U R a L B A S I S O F L Fmentioning
confidence: 99%
“…[43][44][45][46] Despite evidence of the formation of LTB4 in atherosclerotic lesions, 47 to date there have been very few previous studies suggesting that products of 5-lipoxygenase play any role in atherogenesis. 48,49 Aiello et al 35 provide two additional and intriguing observations that suggest that LTB4 mediates leukocyte recruitment into atherosclerotic lesions by indirect mechanisms. First, they demonstrate that the LTB4 receptor antagonist inhibits the LTB4-induced upregulation of CD11b expression in circulating monocytes from the treated mice.…”
Section: See Page 443mentioning
confidence: 99%
“…CD11b is the ␤2 integrin component of the CD11/CD18 complex on monocytes that mediates binding to ICAM-1 as well as to fibrinogen and heparin. 49 It is currently unclear to what extent ICAM-1 contributes to lesion formation as targeted knockout of ICAM-1 in mice only has a modest effect on inhibiting lesion formation. 27 Furthermore, Kubo et al 50 have shown that bone marrow transplantation with CD11b-deficient cells does not inhibit lesion formation in LDLR Ϫ/Ϫ mice.…”
Section: See Page 443mentioning
confidence: 99%